"What We Murmur behind Their Backs": Hidden Transcripts of the North Korean Ruling Elite. Issue 1 (2nd January 2023) - Jung, Jai Kwan; Joo, Hyung-min
ABSTRACT: Based on in-depth interviews with 24 former high-ranking North Korean officials, we investigate the "hidden transcripts" of North Korean ruling elites. After discussing methodical issues in the first section, we analyze the hidden transcripts of the North Korean ruling class in the second section, including their questioning of Chuch'e  ideology, rampant materialism, a "revolution by mouth", and the South Korean wave. If hidden transcripts of powerful officials contain thoughts identical to those of powerless individuals,   for whose benefit  are they hidden? In the third section, we revise the theory of hidden transcripts to answer this question. We conclude by discussing the implications of our findings for the future of North Korea.